philllip1882 1 Posted November 12, 2020 Report Share Posted November 12, 2020 i cant for the llfe of me find the flaw with his logic. somewhere between factoring each polynomial and the step before is wrong. but i see no mistake. 1 Quote Link to post Share on other sites

1 EventHorizon 16 Posted November 12, 2020 Report Share Posted November 12, 2020 Spoiler The error happens when he takes the square root of both sides. (4-9/2)^2 = (-1/2)^2 = (1/2)^2 = (5-9/2)^2 Or more simply... (-1)^2 = (1)^2, take the square root of both sides gives -1 = 1. Except it doesn't! sqrt((-1)^2) = |-1| = |1| = sqrt(1^2) 1 Quote Link to post Share on other sites

0 Martyna 0 Posted November 18, 2020 Report Share Posted November 18, 2020 This is so hard! Quote Link to post Share on other sites

0 pro 0 Posted November 23, 2020 Report Share Posted November 23, 2020 Spoiler so you cant say that just because X^{2} = Y^{2}, X = Y, that would be theoretically incorrect. X^{2} = Y^{2} implies that X = |Y| where |a| or mod(a) denotes +/-a. From there we eliminate the absurdity and only consider the solution for the equation that makes sense Quote Link to post Share on other sites

0 bonanova 85 Posted January 30 Report Share Posted January 30 Spoiler His penultimate line evaluates to (-1/2)^{2} = (1/2)^{2} which is correct: 1/4 = 1/4. But this makes the error stand out: we can't conclude that -1/2 = 1/2 from the equality of their squares. Quote Link to post Share on other sites

## Question

## philllip1882 1

i cant for the llfe of me find the flaw with his logic.

somewhere between factoring each polynomial and the step before is wrong. but i see no mistake.

## Link to post

## Share on other sites

## 4 answers to this question

## Recommended Posts

## Join the conversation

You can post now and register later. If you have an account, sign in now to post with your account.